Ferroptosis in human reproductive tract infections and associated disorders: mechanisms and emerging therapeutic opportunities - Wan, Xinchen; Wang, Xue; Liu, Yanjun; Hong, Longyan; Zhao, Zhandi; Guo, Pengbo (Frontiers in Immunology, 2025)
Ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxidation, is closely associated with mitochondrial damage, diminished glutathione peroxidase 4 activity, dysfunction of the System Xc− cystine/glutamate antiporter, and disruptions in iron metabolism. Infections of the human reproductive system and associated reproductive disorders pose a significant global public health challenge, characterized by diverse pathogens and complex pathogenic mechanisms. Recent research has revealed that ferroptosis plays a critical role in the pathological processes of many of these infections. This review systematically elaborates on the central mechanistic role of ferroptosis in various pathologies of the reproductive system. These include CD4+ T cell depletion and immunological non-response in Human Immunodeficiency Virus (HIV) infection, the development of Human Papillomavirus (HPV)-associated cervical cancer, Staphylococcus aureus-induced endometritis and mastitis, as well as male infertility, pre-eclampsia, and ovarian cancer linked to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Despite the diversity of the pathogens, they can all trigger ferroptosis through common mechanisms, such as disrupting the Nrf2/GPX4 antioxidant axis, impairing the System Xc−–GSH–GPX4 pathway, and inducing dysregulation of iron metabolism. Furthermore, ferroptosis interacts intricately with pyroptosis and apoptosis, forming a complex network that collectively regulates the outcome of infections and the extent of tissue damage. Notably, ferroptosis plays a context-dependent dual role in various reproductive system infections. During the initial phases of infection, it exerts a protective effect by eliminating pathogens and curbing infection progression. In contrast, during advanced or chronic stages, ferroptosis exacerbates tissue injury and promotes disease pathogenesis. The ferroptosis pathway holds great therapeutic promise, either through inhibitors that safeguard host cells or inducers that eradicate drug-resistant bacteria by triggering a “ferroptosis-like” state. Nevertheless, challenges remain for clinical translation, as the ferroptosis network is incompletely understood, and the tissue selectivity and long-term safety of targeted drugs are unverified. Future studies must elucidate host-pathogen interactions to develop precise targeted therapies.